Effect of deficiency thyroid hormone on superoxide dismutase activity enzyme and their related metals in hypothyroid patients in Basrah Governorate/Iraq. - Bushra A.M. AL-Slem (University of Thi-Qar Journal of Science, 2019)
The maintenance of optimal health requires an adequate supply of carbohydrates, proteins and lipids,and macronutrients, micronutrients, and trace elements. The present study evaluates the lack secretion ofthyroid hormones (hyporthyroidism) on antioxidant enzyme which is (superoxide dismutase) and levels ofzinc and copper in serum of Iraqi patients with hypothyroid .The results showed a highly significant decrease(p<0.001) in erythrocyte superoxide dismutase(SOD) activity in patients as compared to control .The level ofzinc decrease significantly in hypothyroid patients compared with control while the level of copper decreasedin patient group compared with control group but no insignificant (p>0.05) . These results indicated thathypothyroidism increased the free radicals due to decreasing the free radicals scavengers.